2020
DOI: 10.3138/cjpe.68866
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key Epistemological Challenges Evaluating in Indigenous Contexts: Achieving Bimaadiziwin through Youth Futures

Abstract: The evaluation field’s understanding of Indigenous ontologies and epistemologies must improve in ways that do not serve to privilege Western ways of knowing, and governmental priorities for accountability. The literature has not identified ways to bridge these in practical ways, nor move the field to balance community and government needs. The paper describes Indigenous ontology and epistemology related to evaluation, then identifies practical challenges bridging Western and Indigenous approaches using the exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The youth on this team have consistently demonstrated that they possess the agential power needed to enhance their community and carve out important roles for themselves within it. These findings align with other research on youth engagement [ 5 , 12 , 20 , 26 ] that indicate how engagement must originate from youth and be on their terms. As researchers, our role is to understand the issues they believe are important and take cues from them about how to best support project activities through their cultural and generational lens, which is the essence of Indigenous Youth Futures.…”
Section: Next Stepssupporting
confidence: 90%
See 1 more Smart Citation
“…The youth on this team have consistently demonstrated that they possess the agential power needed to enhance their community and carve out important roles for themselves within it. These findings align with other research on youth engagement [ 5 , 12 , 20 , 26 ] that indicate how engagement must originate from youth and be on their terms. As researchers, our role is to understand the issues they believe are important and take cues from them about how to best support project activities through their cultural and generational lens, which is the essence of Indigenous Youth Futures.…”
Section: Next Stepssupporting
confidence: 90%
“…Engaging Indigenous youth in research in meaningful ways requires a collaborative, strength-based approach whereby researchers are not leading but facilitating or supporting youth themselves in their efforts [ 26 , 27 ]. Flexibility, ongoing support, and engagement styles that correspond with how youth communicate over time are identified as important to relationship building and creating conditions of trust and engagement in Indigenous contexts [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…T at is our responsibility in addressing the "truth" part of truth and reconciliation" ( Bremner, 2019 , p. 339). Tere is growing interest and work on evaluation in Indigenous contexts, yet there remain gaps in knowledge about how to conduct culturally relevant evaluation that considers Indigenous historical and contemporary context ( Chouinard & Cousins, 2007 ;Shepherd & Graham, 2020 ). Current, efective, collaborative, Indigenous-led research is needed to adapt existing approaches, methods, and tools into those that are culturally relevant and better suited to the needs of diverse Indigenous communities in Canada and elsewhere ( Chandna et al, 2019 ).…”
mentioning
confidence: 99%
“…Within Indigenous contexts, quantitative and acceptability outcomes of an intervention may not be of greatest value to, or may not contribute to the aims, goals, solutions, and outcomes of, Indigenous-led programs or initiatives. Indigenous methodologies focus more on qualitative, relational, behavioural changes rather than on quantitative outcomes ( Shepherd & Graham, 2020 ), with greatest value placed on improved self-determination, cultural identity, and togetherness of the local community ( McKinley, 2020 ). Furthermore, Shepherd and Graham (2020 ) point out that the "western approach treats culture as an independent variable" (p. 445) and that fndings may be generalizable.…”
mentioning
confidence: 99%
See 1 more Smart Citation